2006
DOI: 10.1590/s1516-31802006000400005
|View full text |Cite
|
Sign up to set email alerts
|

Complications and risk factors in transrectal ultrasound-guided prostate biopsies

Abstract: CONTEXT AND OBJECTIVE: Prostate biopsy is not a procedure without risk. There is concern about major complications and which antibiotics are best for routine use before these biopsies. The objective was to determine the rate of complications and the possible risk factors in prostate biopsies. DESIGN AND SETTING: Prospective study, Faculdade de Medicina de Botucatu. METHODS: Transrectal ultrasound (TRUS) guided prostate biopsies were carried out in 174 patients presenting either abnormality in digital rectal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 23 publications
7
31
0
1
Order By: Relevance
“…However, other studies from North America [12,13] reported lower rates of sepsis (0.6%), and an Asian study [14] reported that 0.5% of prostate biopsy cases had fever, similar to the data of our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, other studies from North America [12,13] reported lower rates of sepsis (0.6%), and an Asian study [14] reported that 0.5% of prostate biopsy cases had fever, similar to the data of our study.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies reported that the complication rate of AUR after prostate biopsy ranges from 0.2% to 1.7% [12,[24][25][26][27][28][29][30]. Raaijmakers et al [31] reported that risk factors of urinary retention after prostate biopsy included prostate size, ratio of transition zone size to total size, and an IPSS.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious complications after prostate biopsy are febrile urinary infection and sepsis. After several studies aimed at preventing infections after biopsy, a consensus was reached about prophylaxis with quinolone antibiotics and enema during the procedure [6,[12][13][14][15][16][17][18][19] . Several studies have been conducted in order to avoid sepsis after a diagnostic procedure, which is a life-threatening clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…Simsir et al [11] reported a rate of sepsis of 3.06% in a sample of 2,023 patients in Turkey. De Jesus et al [12] reported a 14.4% rate of post-PB IC consisting of 1.7% sepsis, 9.2% UTI, 0.6% orchitis, and 0.6% prostatitis. A nationwide survey conducted in Japan that included the information from 212,065 PB performed between 2004 and 2006, reported a 2.22% rate of IC, with epididymitis occurring in 0.06%, prostatitis in 0.9%, UTI in 0.09%, and sepsis in 0.07% of the cases [13].…”
Section: Discussionmentioning
confidence: 99%